A rare case report of Morgagni Hernia with Organo-Axial Gastric Volvulus and concomitant Para-esophageal hernia, repaired laparoscopically in a Septuagenarian. (2018) - Mittal, Amol; Pardasani, Madhur; Baral, Sonia; Thakur, Sanjiv
Highlights: These two forms of a hernia form a very rare association. Laparoscopic management of two different pathologies in one setting. Till now only four cases have been reported in English literature with successful Laparoscopic management of this condition. Patients may present with acute life-threatening complications viz. Incarceration, volvulus, etc. Abstract: Introduction: Simultaneous occurrence of Morgagni and the Para-esophageal hernia is a rare clinical condition with eight case reports in the English-language literature and only four managed laparoscopically. We describe a case of a Septuagenarian patient with Morgagni and concomitant Para-esophageal hernia treated laparoscopically. Presentation of a case: A 71-year-old male patient, presented with a one-month history of regurgitation of acid, retrosternal burning and vomiting after eating. Computed tomography (CT) imaging demonstrated a large anterior diaphragmatic hernia, with herniation of bowel loops and anterosuperior displacement of the gastric antrum along with a grade III Para-esophageal hernia. The patient underwent simultaneous laparoscopic repair of Morgagni and Para-esophageal hernia with mesh reinforcement with Nissen's total anti-reflux fundoplication. The patient's postoperative recovery was uneventful. Discussion: A Morgagni Hernia is a rare congenital condition consisting of a Subcosto-sternal defect in the diaphragm. A Para-esophageal hernia is a rare variant of a hiatus hernia. Morgagni and Para-esophageal hernia may present with gastric volvulus or incarceration, requiring emergency treatment. Minimally invasive surgery is the preferred treatment, particularly for elderly patients and patients with comorbidities. The laparoscopic operation can provide excellent exposure and repair the hernia defect easily with minimal invasiveness and fewer complications. Conclusion: This case report highlights the co-existence of Morgagni and Para-esophageal hernias and validates the feasibility of laparoscopic repair of both hernias simultaneously.